Reforming Fixed Asset Accounting in the Public Sector: Global Practices and Policy Insights - Anggraeni, Rasmi Nur; Safitri, Awalina Dea; Adekunle, Ahmed Oluwatobi (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the systemic challenges and reform strategies in fixed asset accounting within public institutions. It examines practices across valuation, depreciation, internal controls, and the implementation of international standards such as IPSAS. Findings reveal persistent issues including bureaucratic resistance, political interference, and outdated technologies. Countries with stronger institutional capacity and digital systems demonstrate better outcomes.This review contributes to the literature by synthesizing international best practices and highlighting policy-relevant insights for sustainable public asset management.